2012
DOI: 10.1186/1471-2164-13-122
|View full text |Cite
|
Sign up to set email alerts
|

Identification of microRNAs from Amur grape (vitis amurensis Rupr.) by deep sequencing and analysis of microRNA variations with bioinformatics

Abstract: BackgroundMicroRNA (miRNA) is a class of functional non-coding small RNA with 19-25 nucleotides in length while Amur grape (Vitis amurensis Rupr.) is an important wild fruit crop with the strongest cold resistance among the Vitis species, is used as an excellent breeding parent for grapevine, and has elicited growing interest in wine production. To date, there is a relatively large number of grapevine miRNAs (vv-miRNAs) from cultivated grapevine varieties such as Vitis vinifera L. and hybrids of V. vinifera an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
69
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 60 publications
(102 reference statements)
16
69
0
Order By: Relevance
“…Our results show that two potential target genes for the two ppemiRNAs had specific cleavage sites corresponding to their miRNA complementary sequences. Furthermore, it was also observed that, consistent with previous reports (Debernardi et al, 2012;Song et al, 2010b;Wang et al, 2012), ppe-miRNA targets have an miRNA-complementary site located in their coding regions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results show that two potential target genes for the two ppemiRNAs had specific cleavage sites corresponding to their miRNA complementary sequences. Furthermore, it was also observed that, consistent with previous reports (Debernardi et al, 2012;Song et al, 2010b;Wang et al, 2012), ppe-miRNA targets have an miRNA-complementary site located in their coding regions.…”
Section: Discussionsupporting
confidence: 89%
“…This allows for the prediction of miRNA targets by computational approaches. Several studies have utilised this fact and identified many target genes in different plant species while allowing 1-3 nucleotide mismatches between the target mRNAs and miRNAs (Song et al, 2009;Wang et al, 2012;Zhang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The majority (70%) of conserved miRNA sequences fell within the 21-nucleotide category (Fig. 3A), one of the most abundant size classes for known grapevine DCL1-derived products Pantaleo et al, 2010;Wang et al, 2012;Belli Kullan et al, 2015). Among novel candidate miRNAs, two major (each above 30%) size categories were observed at 21 and 22 nucleotides (Fig.…”
Section: Mirna Sequencing and Identificationmentioning
confidence: 98%
“…Previous studies identified conserved and novel miRNAs in grapevine (Carra et al, 2009;Mica et al, 2010;Pantaleo et al, 2010Pantaleo et al, , 2016Wang et al, 2012), and a grapevine miRNA expression atlas was published recently (Belli Kullan et al, 2015). However, no studies specifically addressing the identification of drought stress (DS)-responsive miRNAs have been reported in Vitis spp.…”
mentioning
confidence: 99%
“…qRT-PCR is one of the most used techniques for detection of miRNA expression due for its high sensitivity to miRNA detection, the capability to identify single nucleotide changes [53]. miR-RACE (PCR-based) is an effective method to determine the precise sequence of miRNA at their 5´ and 3´ ends, which can distinguish between members of a miRNA family, and they can determine expression patterns at different family member levels [53,54].…”
Section: Mirnas Sequencing and Predictionmentioning
confidence: 99%